A distributed scheduling approach for QoS improvement in cognitive radio networks. (January 2017) - Rathika, P. D; Sophia, S.
Abstract: Allocation of spectrum and its scheduling is difficult in cognitive radio networks, due to the involvement of a greater number of users. Without spectrum allocation, collision increases within the cognitive radio network, and this leads to a high drop rate and degradation of the network performance. To avoid these issues, and for proper spectrum allocation, a new technique is proposed, known as QoS improvement proper scheduling (QIPS). QIPS is used to increase the basic QoS parameters. This proposed technique divides the network into two regions, and each of these regions is allocated its own cognitive radio base station, which allocates proper scheduling on each node under its control. The spectrum is also allocated on a priority basis according to real-time and non-real-time data, and due to this, the network performance is increased. The results of simulations show that, QIPS can be used to decrease the delay, collision probability, end-to-end delay and overhead ratio, and that this scheme also increases network efficiency and throughput.